Microorganisms and fermentation of traditional foods - Ray, Ramesh C.; Montet, Didier (Boca Raton, FL CRC Press, 2015)
"The first volume in a series covering the latest information in microbiology, biotechnology, and food safety aspects, this book is divided into two parts. Part I focuses on fermentation of traditional foods and beverages, such as cereal and milk products from the Orient, Africa, Latin America, and other areas. Part two addresses fermentation biology, discussing specific topics including microbiology and biotechnology of wine and beer, lactic fermented fruits and vegetables, coffee and cocoa fermentation, probiotics, bio-valorization of food wastes, and solid state fermentation in food processing industries"-- Provided by publisher.
"Fermentation is one of the oldest technologies for processing of food and beverages to improve qualities such as extended shelf-life and organoleptic properties. Fermented foods usually have an improved microbial stability and safety, alongwith acceptable taste, and some products can be stored even at ambient temperatures. The common microorganisms used in food fermentations are bacteria, yeasts and molds. The lactic acid bacteria, notably lactobacilli and streptococci are the most commonly found microorganisms in fermented foods, having the ability to produce lactic acid from carbohydrates. Other important bacteria in fermented foods are the acetic acid producing Acetobacter and the Bacillus species. The most important benefi cial yeasts in terms of desirable food fermentations belong to the Saccharomyces family, especially S. cerevisiae. These yeasts play a crucial role in the food industry as they produce enzymes that bring about various desirable biochemical reactions involved in the production of alcoholic beverages. Also, few fungi are usually used to produce a great number of popular cheeses"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Food -- Biotechnology; Food -- Microbiology; Fermentation; Fermented foods